Slenderness limits for fabricated S960 ultra-high-strength steel and composite columns. (August 2019) - Li, Dongxu; Huang, Zhichao; Uy, Brian; Thai, Huu-Tai; Hou, Chao
Abstract: Ultra-high-strength steel (UHSS) has been gaining increasing attention globally due to its significant structural and economic benefits. Specifically, the use of UHSS in steel and composite column sections can reduce the dimensions and self-weight of the structural components. However, the utilisation of UHSS slender sections also renders the structural members more susceptible to local buckling. The reduced ductility as well as less strain hardening of UHSS can also affect the post-buckling load. In order to clarify the local buckling and post-buckling load of compressive members using UHSS plates, the authors herein present an extensive experimental program. A total of sixteen steel and composite specimens are tested with the slenderness limits ( λ ey ) and effective widths ( b e / b ) being identified. Finite element models which account for the effects of residual stress and initial geometric imperfection are developed to capture the buckling behaviour of the box and I-section columns. The enhancement of local buckling and post-local buckling load of UHSS composite sections due to the presence of infilled concrete is demonstrated. In addition, the slenderness limits and effective widths of both bare steel sections and composite sections incorporating UHSS plates are further compared with existing codes of practice. Corresponding design recommendations are consequently provided. Highlights: A total of sixteen stub bare UHSS and composite UHSS columns were tested under axial compression. Experimental results on the slenderness limits for bare UHSS and composite UHSS column were provided. Numerical models were developed to predict the buckling response for bare UHSS and composite UHSS columns. Slenderness limits of bare UHSS and composite UHSS columns are compared with existing codes of practice.